Type of Psychosocial Stressor as Risk Factor of Depressive Symptom in Metabolic Syndrome - Ana Fauziati; Agus Siswanto; Luthfan Budi Purnomo (Faculty of Medicine Universitas Gadjah Mada, 2016)
Background: Metabolic syndrome and depression are two major diseases over the world, which are increasing in prevalence over time. Depression is major mental health burden over the world. In long time, depression can lead to metabolic syndrome, while metabolic syndrome is risk factor for developing depression. Chronic stress that induced by psychosocialstressor lead to the development of both metabolic syndrome and depression. Further research is important to identify which type of psychosocial stressor is the risk factor for depression symptom in patient with metabolic syndrome.Aims: This study is to identify the type of psychosocial stressor which could be the risk factor for depressive symptom.Method: The study design was case control. The case group consisted of metabolic syndrome patients with depressive symptom, while the control group consisted of metabolic syndrome patients without depressive symptom. Metabolic syndrome was diagnosed based on International Diabetes Federation (IDF) criteria. Depressive symptom was measured by Beck Depression Inventory (BDI). Psychosocial stressors were measured by Stressful Life Events (SLE) questionnaire. Dependent variable was depressive symptom, while independent variables were type of psychosocial stressors (finance, work, social relationship, health and housing). Analysis methods that used in this study were independent t test, Pearson/Spearman correlation analysis, chi square and logistic regression.Result: There were 54 patients in this study, consisted of 24 in case group and 30 incontrol group. There was no significant difference in most basic characteristics between two groups. There was significant difference of SLE score between two groups. Chi square analysis showed that housing, finance, health, social relationship, and work stressors were risk factors fordeveloping depressive symptom in metabolic syndrome (OR 24.5; 9.7; 8.4; 5.4; 3.9 respectively, significant). Demographic factor which also influenced depressive symptoms was salary less than 1 million per month (OR 45, significant). According to logistic regression analysis, psychosocial stressors which most influenced the depressive symptom were finance and housing.Conclusion: The study showed that housing, finance, health, social relationship and work stressors were risk factors for developing depressive symptomp in metabolic syndrome.